Parameter Design for the Energy-Regeneration System of Series Hydraulic-Hybrid Bus - SONG Yunpu (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
This paper simplifies the energy recovery process in the series hydraulic hybrid bus’ energy regeneration system into a process in which the main axle’s moment of inertia drives the secondary element variable delivery pump/motor and brings hydraulic oil from the oil tank to the accumulator. This process enables braking of the vehicle and also allows recovery of energy to the accumulator. Based on the flow equation for the secondary element variable delivery pump/motor and the torque equilibrium equation for its axle, the force equilibrium equation for vehicle braking and the pressure variation and flow continuity equations for the accumulator, simulation studies are conducted to analyze the effects of various system parameters, such as accumulator capacity, displacement of the secondary element variable delivery pump/motor, initial operating pressure of the system, etc. on system performance during regenerative braking. DOI: http://dx.doi.org/10.11591/telkomnika.v10i6.1420